Peptide Epimerization Machineries Found in Microorganisms - Ogasawara, Yasushi; Dairi, Tohru (Frontiers in Microbiology, 2018)
D-Amino acid residues have been identified in peptides from a variety of eukaryotes and prokaryotes. In microorganisms, UDP-N-acetylmuramic acid pentapeptide (UDP-MurNAc-L-Ala-D-Glu-meso-diaminopimelate-D-Ala-D-Ala), a unit of peptidoglycan, is a representative. During its biosynthesis, D-Ala and D-Glu are generally supplied by racemases from the corresponding isomers. However, we recently identified a unique unidirectional L-Glu epimerase catalyzing the epimerization of the terminal L-Glu of UDP-MurNAc-L-Ala-L-Glu. Several such enzymes, introducing D-amino acid resides into peptides via epimerization, have been reported to date. This includes a L-Ala-D/L-Glu epimerase, which is possibly used during peptidoglycan degradation. In bacterial primary metabolisms, to the best of our knowledge, these two machineries are the only examples of peptide epimerization. However, a variety of peptides containing D-amino acid residues have been isolated from microorganisms as secondary metabolites. Their biosynthetic mechanisms have been studied and three different peptide epimerization machineries have been reported. The first is non-ribosomal peptide synthetase (NRPS). Excellent studies with dissected modules of gramicidin synthetase and tyrocidine synthetase revealed the reactions of the epimerization domains embedded in the enzymes. The obtained information is still utilized to predict epimerization domains in uncharacterized NRPSs. The second includes the biosynthetic enzymes of lantibiotics, which are ribosome-dependently supplied peptide antibiotics containing polycyclic thioether amino acids (lanthionines). A mechanism for the formation of the D-Ala moiety in lanthionine by two enzymes, dehydratases catalyzing the conversion of L-Ser into dehydroalanine and enzymes catalyzing nucleophilic attack of the thiol of cysteine into dehydroalanine, was clarified. Similarly, the formation of a D-Ala residue by reduction of the dehydroalanine residue was also reported. The last type of machinery includes radical-S-adenosylmethionine (rSAM)-dependent enzymes, which catalyze a variety of radical-mediated chemical transformations. In the biosynthesis of polytheonamide, a marine sponge-derived and ribosome-dependently supplied peptide composed of 48 amino acids, a rSAM enzyme (PoyD) is responsible for unidirectional epimerizations of multiple different amino acids in the precursor peptide. In this review, we briefly summarize the discovery and current mechanistic understanding of these peptide epimerization enzymes.